Food variety and its contributing factors among public university students in Klang Valley - Suhaimi, Tatiana; Sulaiman, Norhasmah; Osman, Syuhaily (Malaysian Consumer and Family Economics Association, 2017)
This study was conducted to determine the contributing factors towards food variety among public university students in Klang Valley. A total of 400 students from Universiti Putra Malaysia, International Islamic University Malaysia, Universiti Kebangsaan Malaysia, and Universiti Teknologi Mara were chosen using multistage random sampling. Accordingly, a face-to-face interview was conducted with the students to obtain information on the (i) demographic characteristics, (ii) food choice‘s motive, (iii) food neophobia, (iv) social support, (v) emotion, (vi) nutritional knowledge, and (vii) food variety. The data were analysed using descriptive and multivariate analyses with the application of binary logistic regression via Statistical Package for the Social Sciences (SPSS). This study found that a majority of the students (95.25 %) had a low level of food variety, particularly in every food group such as (i) cereal and grains (96.75 %), (ii) meats and poultry (79.25 %), (iii) fish and seafood (91.50 %), (iv) milk and dairy products (93.25 %), (v) legumes (85.25 %), (vi) vegetables (75.25 %), and (vii) fruits (93.50 %). Furthermore, the results from binary logistic regression showed that the respondents who chose food based on sensory motive and those who were in the neophobic category had 1.54 and 5.55 likelihood to have low level food variety, respectively. Plus, the respondents with high level of nutritional knowledge were 5.40 more likely to have low level of food variety compared to their counterparts. In order to address these issues, it is highly recommended for relevant ministries, financial education agencies, and universities to collaborate and plan intervention programmes on increasing food variety among university students without compromising their food budget.